BELA DIRI DALAM KASUS PEMBEGALAN BERMOTOR YANG MENYEBABKAN MATINYA PELAKU - Ronal Nelson; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
We often hear about murder both social media and in print media, namely the journey of the Amaq Sinta case that killed two robbers, becoming a suspect until finally released. Criminal Law contains about having to be done and is also prohibited from causing a sanction such as punishment. The formulation of the problem of criminal acts that can be categorized as forced defense and How the application of Article 49 paragraph 2 is seen in the case in Indonesia.